PENYULUHAN KESEHATAN MENGENAI PENTINGNYA SALURAN PEMBUANGAN AIR LIMBAH RUMAH TANGGA DI DESA SIABU KECAMATAN SALO - Ade Dita Puteri; Devina Yuristin (COVIT (Community Service of Health), 2021)
Water is a basic need for life, especially for humans who always need water throughout their lives. The human body is mostly made up of water. Household waste is waste that comes from kitchens, bathrooms, laundry, household industrial waste and human waste. the majority of the population in Siabu Village do not know how to manage waste and the majority of waste water disposal facilities are inadequate. Health Counseling Regarding the Importance of Household Wastewater Sewerage in Siabu Village, Salo District, which can be identified in several specific problems, namely: Is there an effect of Health Counseling Regarding the Importance of Wastewater Sewerage for Communities in Siabu Village, Salo District. However, after participating in community outreach activities, they will be able to find out the type of wastewater, where the wastewater comes from, how to manage wastewater and the impact of wastewater on health. Health education activities (counseling) about the importance of sewerage in general went smoothly. The counseling participants were representatives of residents, RT heads and health cadres, as many as 82 people. The place used for this activity is the Siabu Village Hall. This activity will be carried out using several methods, namely asking questions and answering questions to participants. . With this counseling, it is hoped that there will be sustainable activities so that it can further increase public knowledge. Keywords : wastewater ; Counseling